Genetic diversity of redclaw crayfish Cherax quadricarinatus von Martens 1868 using 16S mitochondrial DNA marker. Issue 1 (November 2021) - Mohd Dali, M Z; Aidi, Q; Mohd Nasir, M S A; Ismail, N; Kamarudin, A S
Abstract: There have been reported around 11 aquatic invasive alien species (IAS) found in Malaysian waters. Cherax quadricarinatus, or commonly known as Australian redclaw crayfish, is one of the invasive species. C. quadricarinatus has the potential of causing negative impacts ecologically and economically in the local environment as it has reported in several countries if they get established and not monitored properly. Habitat alteration, native species depletion and spreading of diseases are among the reported negative impacts of C. quadricarinatus . This study was conducted with the aim to assess the genetic diversity of C. quadricarinatus from 4 different populations. Uncovering the diversity and population structure of the redclaw crayfish will help in enhancing the understanding of adaptation and survival of C. quadricarinatus . Thus, the information can be used in monitoring and management of this invasive crayfish in future. DNA of C. quadricarinatus was successfully extracted from its tissue and amplified via polymerase chain reaction (PCR) using mitochondrial DNA (mtDNA) 16S gene then proceeded for sequencing and analysed using several genetic analysis software to understand the diversity, phylogeny and population structure of this invasive crayfish species. A total of 493 bp fragments of 32 samples from four sampling sites were obtained. Four haplotypes were observed which Hap-1 was the most common haplotype. The highest genetic variation is Selangor (Pi = 0.00248, Hd = 0.694). However, low levels of both haplotype and nucleotide diversity indicates the loss of genetic diversity. Analysis of molecular variance (AMOVA) results revealed that the percentage of genetic variation within the population was 69.58% while among populations was 30.42%, indicating significant genetic differentiation among population (P < 0.05). The maximum likelihood tree showed that all haplotypes were clustered and grouped together with United States, Czech Republic, China and Australia.